HUBUNGAN ANTARA POLA ASUH ORANG TUA DENGAN KEPERCAYAAN DIRI PADA REMAJA DI MTSN 1 KAMPAR - NENENG FITRIA NINGSIH; SITI HOTNA SIAGIAN (Jurnal Ners, 2022)
Adolescence is a period of transition from childhood to adulthood, where adolescence is also referred to as a period of change both physically and psychologically. From a psychosocial point of view, in the adolescent phase, there are often many demands and pressures shown on adolescents, for example, a teenager who has self-confidence can suddenly turn into doubtful and even lose confidence. Self-confidence in adolescents is caused by several factors, both environmental factors and family factors. Self-confidence in adolescents is very important for the development of talents and interests as well as potential that will be seen with the potential and good achievements of these adolescents. This belief will make a person feel that he is able to achieve various goals in life so that self-confidence is a belief and belief in the abilities and potential possessed by a person in a form of personality and positive feelings. The purpose of this study was to determine the relationship between parenting and self-confidence in adolescents at MTSN 1 Kampar. This type of research was quantitative using analytic correlation research with a cross sectional approach. The data analysis used was univariate (central tendency) and bivariate (chi square test). It is recommended for community respondents to improve good parenting for their children so that they are able to produce teenagers who have positive self-confidence.